Determinasi Pertanian, Industri dan Perdagangan Terhadap Pengurangan Tingkat Kemiskinan di Nusa Tengara Barat Tahun 2018-2022 - Faqih, Azfar; Hidayat, Nanda Nur; Ardiansyah, Julian; Cahya, Refin Dwi; Situmorang, Ricardo; Maulana, Yoga Tri (Fakultas Sains & Teknologi, Universitas Labuhanbatu, 2024)
The most serious problem faced by a country in realizing economic development is poverty. This study was conducted to see the effect of agriculture, industry, and trade on poverty reduction. The method used is the static panel regression method to analyze the relationship and influence of the independent variable on the dependent variable. The results showed that there was a negative effect of the agricultural sector on the poverty rate and there was a positive effect of the industrial sector on poverty, but the trade sector had no effect on poverty. Then simultaneously the agricultural, industrial, and trade sectors affect the poverty rate.